THE DEVELOPMENT OF THE FUTURE PEDAGOGUES‘ MOTIVATIONAL SPHERE DURING MASTERS STUDYING - Batechko, N. G. (Continuing Professional Education: Theory and Practice, 2019)
The article reveals peculiarities in motivational sphere forming of future higher educational institution teachers during masters studying. On acmesinergetic basis the methodological ground of future pedagogue’s motivation sphere development was represented. Examined the process of masters’ motivation sphere stimulation, pedagogical conditions that help to do it. Examined the benefits of masters’ programs in the formation of motivated students’ readiness for pedagogical activity. The future pedagogues‘ motivational sphere forming by magistracy obtains effectiveness if it realizes according to the elaborated and grounded theoretical and methodological principles that disclose the directions of the contradictions overcoming in the evolution of the motivational readiness to the postgraduates‘ pedagogical work; take into account the advantages of the studying in the magistracy; implement the andragogical principles of the postgraduates’ education. The psychological aspects of the awareness by future pedagogue the necessity of the self education and selfdevelopment motivate the further professional work and develop the creative potential.